2015
DOI: 10.1111/micc.12218
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Capillary Loop Hemoglobin Spectroscopy in Labial, Sublingual, and Periodontal Tissues

Abstract: In vivo spectroscopic hemoglobin optical density ratios in oral mucosal microvessels show a qualitatively consistent result within the expected in vitro parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The altered architecture of microvessels in tissues lining the periodontal pocket with development of elongated venules can contribute to the low hemoglobin oxygen saturation found in chronic periodontitis 25 , 33 . However, these changes appear relatively late in the destructive process, unlike the dilation and increased flow, which are features of the inflammatory process that have been shown to occur in the early stages of gingivitis 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The altered architecture of microvessels in tissues lining the periodontal pocket with development of elongated venules can contribute to the low hemoglobin oxygen saturation found in chronic periodontitis 25 , 33 . However, these changes appear relatively late in the destructive process, unlike the dilation and increased flow, which are features of the inflammatory process that have been shown to occur in the early stages of gingivitis 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of the oral mucosa in the labial tissues can be as little as 100 μm and is supported by a very loose submucosa, which makes tissues very flexible 23 , 24 . This means that if the 1‐mm diameter imaging lens and 1‐mm diameter illuminating optical fiber are positioned 600 μm apart and placed in contact with the labial mucosa, a small fold of the mucosa will fall between the lens and fiber to allow transillumination of the microvessels supplying the mucosa 25 . The relatively thick section with diffraction of light within the tissues means that the effective source of the light is the tissues immediately deep to the object plane (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…MSI oximetry has been applied to diverse applications in vivo, including measurement of blood OS in the spinal cord [7], the brain [8], muscle tendons [9,10], the bowel [11], the oral microvasculature [12], and the skin [13]. In the eye, MSI oximetry has established the oxygen dynamics and physiological norms of the retina [6], the choroid [14], the bulbar conjunctiva [15], and the episcleral blood vessels [15].…”
Section: The Application and Utility Of Multispectral Imaging (Msi) O...mentioning
confidence: 99%
“…However, the anatomy of the human gingival vasculature has only recently been fully described in detail with little functional assessment [ 19 ]. We have previously shown that capillary loops in tissues affected by periodontal breakdown contain predominantly deoxygenated blood and that these loops have no evidence of an intact glycocalyx, suggesting the presence of venous capillary loops [ 20 21 ]. This has increased our knowledge of the disease process, but gives no indication of why some people develop periodontal breakdown whilst others do not progress beyond gingival inflammation.…”
Section: Introductionmentioning
confidence: 99%